Influence of maternal infection caused by Klebsialle pneumonia on morphologic and functional state of fetuses’ adrenal glands cortex (experimental research). - Tovazhnianska, V. D.; Sorokina, I. V.; Yakovtsova, I. I. (Морфологія / Morphologia / Morfologìâ, 2016)
Background. Infections of fetuses and newborns caused by Klebsiella themselves and in polymicrobial associations have short incubation period, as well as a high percentage of deaths. Intrauterine infection of fetus and fetal chronic hypoxia should be considered as conditions that require a lot of adaptive changes where one of the most important roles is performed by adrenal glands. Objective: to identify the influence of mother infection caused by K.pneumoniae on fetal adrenal cortex. Methods: During the experiment, laboratory rats were divided into 3 groups. Group 1 - control - pregnant rats lived in physiological conditions. Group 2 - modeling of chronic intrauterine hypoxia - pregnant rats throughout pregnancy (21 days) were subjected to a daily high altitude hypoxia. Group 3 – modeling of infection – using the infective dose of Klebsiella pneumonia was modeled. Then male were tucked to infected female, females got pregnant. All rats were removed from the experiment on the last stages of gestation in order to extract fetus for further study. The adrenal glands of fetuses were examined using histological, morphometric and immunohistochemical methods. Results. Infectious pathology of mother has a more detrimental effect on fetal adrenal glands, than "pure" chronic intrauterine hypoxia. In group 3 hypoplasia is more pronounced in zona glomeruloza. Severe lesions of cytolysis and resorption of cell with increasing of cortisol production are seen in zone fasciculata. In fetal zone there are depletion of functional activity, zone is decreasing and has a tendency to decrease hormone production. Conclusion: when mother is infected by Klebsiella pneumonia in constant and fetal adrenal cortical areas of fetus changes manifested by hypoplasia of zona glomeruloza, hyperactivity of zona fasciculata and depletion of functional activity in fetal zone.